[Rezension von: Falina, Maria, Religion and politics in interwar Yugoslavia : Serbian nationalism and East Orthodox Christianity] - Oset, Željko (A journal of church and state, 2025)
Maria Falina’s Religion and Politics in Interwar Yugoslavia: Serbian Nationalism and East Orthodox Christianity offers a theoretically rich and empirically